If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -26 = -20 + 2x Reorder the terms: -26 + 5x = -20 + 2x Solving -26 + 5x = -20 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -26 + 5x + -2x = -20 + 2x + -2x Combine like terms: 5x + -2x = 3x -26 + 3x = -20 + 2x + -2x Combine like terms: 2x + -2x = 0 -26 + 3x = -20 + 0 -26 + 3x = -20 Add '26' to each side of the equation. -26 + 26 + 3x = -20 + 26 Combine like terms: -26 + 26 = 0 0 + 3x = -20 + 26 3x = -20 + 26 Combine like terms: -20 + 26 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| 4/9*7/3 | | 7x/5+x=84 | | f(x)=x^2-12x+39 | | 3*2/7 | | 7(3x-14)=-77 | | 23+3y-2=13y-14-5y | | 9*z=9 | | x=3y+12 | | 4p-22=-40+6p | | 15x-3=40x+12 | | x+20+3x=-16-3x-20 | | x-0.6=9.38 | | 3x-23=-43+8x | | -(2x+11)=-21 | | -37x= | | 9(3y+1)=4y-5y | | 9(3x+1)=4y-5y | | 2(r-4)=6(r+4) | | 4(3+6x)-4=80 | | 6(2x-2)= | | x/9-2=-6 | | 22r*2+69r=8 | | -2y-1=-9 | | 4y-6=-26 | | 3.5+x=8 | | 64/130=55/x | | 9-(3y-2)=5-4y | | 10+x^2=11 | | 11y+9-5y=-15 | | 34.8/1000 | | a=d+pm | | -3.4/p=-0.06 |